Соціальний контакт як складова громадського простору міста - Сулик, Тарас; Sulyk, Taras (Видавництво Львівської політехніки, 2023)
Розглянуто важливість соціального контакту в громадських просторах міст. Проаналізовано особливості соціальних контактів, які можуть виникати в громадських просторах міста та описано потребу у врахуванні складової соціального контакту на рівні з забезпеченням його функціонального наповнення. Як наслідок, визначено основні види соціального контакту в умовах урбаністичного середовища, а також розглянуто способи його забезпечення в громадських просторах міста.

This article examines social contact as an important component of public space in cities. The author emphasizes the physical parameters of space that influence the possibility and quality of social interactions. Street networks and sidewalk accessibility contribute to encounters and communication in densely populated areas, while large open spaces without buildings may reduce the number of social contacts. Space design, such as the presence of public squares and parks, can increase social encounters and make the space more diverse. Building planning with eye-level windows for passersby can also promote interaction between people inside the building and pedestrians. To ensure an equal quantity and quality of social contact in the public space of a city, it is necessary to understand the forms of social interaction and their impact on the comfort of the urban environment. Formal, informal, and technical levels of interaction among people in society are distinguished. The article discusses social contact in physical public space, architectural environments, and the interaction between individuals and spatial elements. The classification of forms of social contact includes direct, involuntary, visual, navigational, and acoustic contacts, depending on the distance between participants. The presence of quality social contact in public space affects safety, health, social support, cultural environment, and the overall atmosphere of a city. Public spaces with open areas located at the intersection of different environments can become platforms for a healthy cultural and educational environment in a city. Ensuring social contact in public space is of great importance for the development of cities and improving the quality of the city life. When designing urban environments, it is essential to consider not only the physical parameters of space but also the aspects of social contact. It is important to design spaces that promote encounters, communication, and interaction among people.
Social contact as a component of public city space
Keywords: громадський простір; соціальний контакт; архітектура громадського простору; public space; social contact; architecture of public space; 721